Spatial distribution of banks in Istanbul - E.Ümran Topçu (European Regional Science Association (ERSA), 2001)
This study searched the spatial distribution of banks in order to investigate the transformation of istanbul from a monocentric to a polycentric city. As a result , it has been found out that the old cbd has lost its dominant facilitiesc such as population , employment etc. New centres have been growing rapidly on some peripheral districts. An important explanation of the decentralization is the transformation of the economy of istanbul , which now requires large and modern office space and private car transport , that the old cbd can no more provide.de.
Keywords: 330